Adaptive and User-Centered HCI for Intelligent Technologies: A Global Perspective - Abdurrohman (Digitus : Journal of Computer Science Applications, 2024)
Human-Computer Interaction (HCI) within intelligent systems plays a critical role in shaping user experience, particularly through effective design, usability, and accessibility. This narrative review aims to synthesize current research trends and challenges in designing inclusive and adaptive HCI environments. Literature was gathered from Scopus and Google Scholar using keywords such as "Human-Computer Interaction," "Intelligent Systems," "Usability," "Accessibility," and "User-Centered Design." Articles were selected based on inclusion criteria focusing on recent, peer-reviewed studies that explore empirical, review, and case-based methodologies. The results highlight that effective user interface design is rooted in multimodal, emotionally aware, and cognitively efficient interactions. AI-enhanced features and adaptive layouts contribute to a more intuitive experience, particularly in healthcare and smart vehicle environments. Usability assessments, including the System Usability Scale and A/B testing, further validate user engagement and system effectiveness. Accessibility remains a crucial yet underrepresented theme, with a significant disparity in inclusive design for vulnerable populations. Notably, best practices from countries with strong accessibility policies underscore the importance of integrating users with disabilities into the design process. The discussion points to systemic factors—such as regulatory frameworks, digital literacy, and funding priorities—as both barriers and enablers of progress. To bridge existing gaps, the study recommends further longitudinal, cross-cultural, and inclusive research. Strengthening digital education and accessibility policies is key to enhancing user-centered innovation in intelligent systems.